GORING TRAUMA IN A PREGNANCY RESULTING UTERINE RUPTURE: A CASE REPORT - Tinkishea, Ermias Abate; Teka, Hale; Awash, Teweldebirhan; Gebre, Solomon (Ethiopian Journal of Reproductive Health, 2019)
ABSTRACT BACKGROUND: Trauma in pregnancy is the leading cause of non-obstetric maternal mortality, with 20% of maternal deaths directly attribute to the injuries. The most common cause of trauma in pregnancy is motor vehicle accident and domestic violence. Other causes of trauma in pregnant patients are penetrating injuries and falling down accidents. The incidence of maternal visceral injury with penetrating abdominal trauma is only 15% to 40% compared with 80% to 90% in non-pregnant women. Goring injury during the pregnancy is the least reported cause of trauma in pregnancy. CASE PRESENTATION: 42-year-old Gravid V Para IV mother with gestational age of 30 weeks +2 days referred from primary hospital with a diagnosis of 2nd trimester pregnancy and blunt abdominal trauma. She complained goring injury to the lower abdomen of 15 hours duration. On physical examination, she was acutely sick looking with tender abdomen but superficial lacerations or bruises. Focused Abdominal Sonography for Trauma showed ruptured uterus with significant peritoneal collection. With the impression of uterine rupture she was operated at Axum Comprehensive specialized hospital with intraoperative finding of intact skin with bridged fascia. The uterus completely ruptured on the anterior lower uterine segment (10 cm) with freshly dead fetus in the peritoneal cavity. Following standard procedures uterus was repaired in two layers and patient’s post operative course was unremarkable. Conclusion: Trauma in pregnancy is a common phenomenon; however, it is unusual to find goring injury in pregnancy. It is one of the penetrating types of trauma with catastrophic complication to the mother and fetus. So, we need to have high index of suspicion of uterine rupture in case of such kind of circumstances. KEYWORDS: trauma, pregnancy, goring injury, uterine rupture (Ethiopian Journal of Reproductive Health; 2019; 11;2:61-65)